Enzyme Histochemistry of Eyelids in Buffalo Fetuses (Bubalus bubalis) - Tomar, M.P.S. (Indian Journal of Veterinary Anatomy, 2019)
Present study was planned on the enzyme histochemistry of eyelids of buffalo fetuses. The fresh samples from eyelids were collected and kept at -20 0C and later subjected for cryostat sections. These sections were incubated for suitable substrate for various enzymes. The enzyme histochemical picture of various component of eyelids viz. epidermis, dermis, sebaceous glands, tarsal glands, orbicularis oculi muscle, hair follicle and other structures showed a spectrum of reactions with different enzymes. The activity of tyrosinase and DOPAoxidase was noticed in the epidermis only whereas the reaction for the presence of carbonic anhydrase was encountered in tarsal glands with a low intensity. Remaining all the components showed various degrees of reactions with various substances, which may be indicative of their functional significance.